ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI IMPOR TEH DI INDONESIA TAHUN 2000-2018 - Oktavia Sucitra; Ekwarso Hendro; Darmayuda Darmayuda (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to analyze and determine the effect of the real exchange rate of US Dollar and national income per capita on tea imports in Indonesia in 2000-2018. The variables observed in this study were the volume of tea imports as the dependent variable, then the real exchange rate and national income per capita as independent variables. This study uses secondary data that is time series in annual form starting from 2000-2018 obtained through the publication of the Central Statistics Agency, Bank Indonesia, the Ministry of Agriculture, and the World Bank. The model uses time series data which is calculated using multiple regression method using the Eviews 10 application. The results show that simultaneously the real exchange rate variable and the national income per capita have a significant effect on tea imports in Indonesia in 2000-2018. Partially, the real exchange rate variable has a negative and insignificant effect on tea imports in Indonesia, while the national income per capita variable has a positive and significant effect on tea imports in Indonesia in 2000-2018.Keywords: Imports, Rupiah real exchange rate against US dollar, National Income per capita